2010
DOI: 10.1074/mcp.m900628-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Accuracy and Precision Issues in iTRAQ Quantitation

Abstract: iTRAQ (isobaric tags for relative or absolute quantitation) is a mass spectrometry technology that allows quantitative comparison of protein abundance by measuring peak intensities of reporter ions released from iTRAQ-tagged peptides by fragmentation during MS/MS. However, current data analysis techniques for iTRAQ struggle to report reliable relative protein abundance estimates and suffer with problems of precision and accuracy. The precision of the data is affected by variance heterogeneity: low signal data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

24
459
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 466 publications
(488 citation statements)
references
References 42 publications
(73 reference statements)
24
459
3
Order By: Relevance
“…Several studies have shown that iTRAQ labeling is associated with bias; fold changes are compressed toward one (11)(12)(13)(14). It has been suggested that this underestimation of fold change is caused by co-eluting peptides with similar m/z values that are isolated together, creating mixed iTRAQ intensities in complex samples (14).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have shown that iTRAQ labeling is associated with bias; fold changes are compressed toward one (11)(12)(13)(14). It has been suggested that this underestimation of fold change is caused by co-eluting peptides with similar m/z values that are isolated together, creating mixed iTRAQ intensities in complex samples (14).…”
mentioning
confidence: 99%
“…Spike-in of proteins has the benefit of looking at a small controlled set of peptides and how they behave in the studied system. This strategy has been used in several of the previously mentioned papers that address iTRAQ quantification (11)(12)(13)(14). However, the number of data points studied may be unlikely to represent the complexity of a real biological sample, which often contains thousands of proteins (24).…”
mentioning
confidence: 99%
See 3 more Smart Citations